Hubungan Tingkat Aktivitas Fisik Dengan Resiko Terjadi Demensia Pada Lansia Di Posyandu Lansia RW 03 Kelurahan Dinoyo - Ega Halima Ramdini; Siti Ainun Ma’rufa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: The prevalence of elderly people continues to increase every year. This is directly proportional to the problems that continue to occur. One of them is a decrease in cognitive abilities which results in dementia. One of the risk factors for dementia is the level of physical activity. Decreased physical activity is believed to be one of the causes of dementia in the elderly, along with other risk factors. Objective: To determine the relationship between physical activity levels and risk factors for dementia in elderly posyandu participants in RW 03, Dinoyo Village. Research Method: This research uses descriptive analytical methods with a cross-sectional design. The method with sampling of both variables is carried out in the same time period. The total sample was 51 elderly posyandu participants in RW 03 Dinoyo Village who met the inclusion criteria. The measurement instrument uses the IPAQ-SF questionnaire to measure physical activity levels and the MMSE questionnaire to measure cognitive abilities. The correlation test used the Spearman Rho test with IBM SPSS 25. Results: Based on the Spearman Rho correlation test, the result was p = 0.339 (p > 0.05). The results showed that there was no relationship between the level of physical activity and the risk of dementia. Conclusion: There is no significant relationship between the level of physical activity and the risk of dementia in respondents. The lack of results in this study was caused by several factors, namely the limited research design and other supporting factors that were not studied.